A meso-mechanical constitutive model of bulk metallic glass composites considering the local failure of matrix. (April 2019) - Rao, Wei; Zhang, Juan; Kang, Guozheng; Yu, Chao; Jiang, Han
Abstract: Referring to the existing experimental investigation, a meso-mechanical constitutive model is constructed to describe the deformation and failure of bulk metallic glass composites under the monotonic uniaxial tensile and compressive loading conditions. Firstly, a free volume based constitutive model considering the failure mechanisms of bulk metallic glass and a unified visco-plastic model are employed for the bulk metallic glass matrix and toughening phase, respectively. To effectively reflect the local failure occurring in the bulk metallic glass matrix of the composites, a new two-leveled homogenization method is developed by extending the traditional Mori-Tanaka's method. Then, the algorithmic tangent operators for both of bulk metallic glass matrix and toughening phase are derived; the numerical integration algorithm of proposed model is also developed. Finally, the effectiveness of proposed model is validated by predicting the deformation and failure of bulk metallic glass composites under the monotonic tension and compression, respectively. Comparison of predicted results and corresponding experimental ones demonstrates that the proposed model can predict the deformation and local failure of bulk metallic glass composites well. Highlights: Meso-mechanical constitutive model for BMGCs with considering the local failure of matrix is constructed. Two-leveled homogenization method is developed to reflect the local failure occurring in the matrix of BMGCs. Deformation and failure of BMGCs can be reasonably described by the developed constitutive model.